CRITICAL LISTENING DEFICITS IN HIGHER EDUCATION: A SYSTEMATIC REVIEW OF METACOGNITIVE GAPS, ARGUMENT EVALUATION, AND LEARNING ANXIETY - Gaffar, Muh Syukri; Sultan; Pahar, Usman (Curricula: Journal of Teaching and Learning, 2026)
Critical listening is a high-level language skill that plays an important role in the academic success of students in higher education. However, research that explicitly discusses the problem of critical listening in students is still widespread and has not been systematically mapped. This research aims to identify and synthesize the problem of critical listening in university students through the Systematic Literature Review (SLR) approach. This study refers to the PRISMA 2020 guidelines with data sources coming from the ScienceDirect database, Taylor & Francis Online, and the Education Resources Information Center (ERIC). Literature searches are limited to peer-reviewed journal articles published in the 2021–2025 range. Of the total 674 articles identified, 9 articles met the inclusion criteria and were further analyzed. The results of the synthesis show that students critical listening problems include the limitations of advanced metacognitive strategies, low evaluation ability of oral arguments, the influence of affective factors such as listening anxiety and cognitive load, and listening learning designs that are not yet oriented towards critical thinking. The contribution of this research lies in presenting the latest systematic mapping of the problems of critical listening in higher education students, as well as offering a conceptual framework based on literature findings that can be the basis for the development of a critical listening learning model that is integrated with metacognitive strategies, argumentative evaluation, and learning reflection. This research emphasizes the need to develop listening learning that explicitly integrates metacognitive strategies, critical evaluation, and reflection in the context of higher education.